Development of Mobile Application Software for Compulsory Acquisition and Compensation in Niger State, Nigeria - Nwokenkwo, C. B.; Lasisi, J. O.; Mohammed, J. K. (International Journal of Real Estate, 2026)
The recent mass road development by Niger State government poses some challenges to professionals involved in the construction process including Estate Surveyors and Valuers as they involved compulsory acquisition of lands with unexhausted improvement on them. One of the major challenges of Estate Surveyors and Valuers on the project is the short time duration for submission of assessment report for compulsory acquisition and compensation. It is therefore, imperative to deploy technology to improve the compulsory acquisition and compensation process in Niger State, Nigeria. It was based on this background that the research intends to develop mobile application software for compulsory acquisition and compensation for Niger State. The mobile application software serve as a template for compulsory acquisition and compensation process by the professionals in the state. Data were collected on the current land acquisition and compensation process in Niger State, through reconnaissance survey, interview of the Estate Surveyors and Valuers on the software currently being used for compulsory acquisition and compensation and the appropriate state authorities to know the applicable rate as it relates to the unexhausted improvement. The result provided user friendly mobile software on Android platform for compulsory acquisition and compensation, accurate data collected from the properties to be compensated, accuracy of valuation method and adopted rate for the valuation practical use of the software. The finding of this study was expected to add value to the existing procedure for compulsory acquisition and compensation in Nigeria and contribute to the existing literature by designing and implementing mobile application software, particularly, for field inspection, data collection, computation and reporting in order to achieve efficient and adequate compensation.